Effectiveness of Length and Weight Growth of Tenebrio molitor L. Larvae with Plastic Waste Feeding - Hashifah, Fathimah Nurfithri; Muslihah, Niken Istikhari; Khafida, Wilda; Haryanto, Trisno; Ambarningrum, Trisnowati Budi (Jurnal Biologi Tropis, 2024)
Inorganic waste accumulating in plastic waste, including styrofoam, which has accumulated in large quantities in waste disposal sites (TPS), is challenging to decompose into the environment. Black beetles (Tenebrio molitor) are insects that decompose inorganic waste and can decompose polystyrene waste. The presence of bacteria in the digestion of insects contributes to the decomposition of plastic waste in the form of styrofoam. This study aimed to determine how effective the larvae of T. molitor are in degrading polystyrene waste (styrofoam) through larval development from the process of nine instar stages. In order to develop more prospective larvae, the research was conducted in multiple stages, including initial maintenance and treatment as well as data gathering to test the growth of larval length. The results are known from the length of the larval body, and it is hoped that the larvae can later be used to help decompose small to large-scale styrofoam waste discharged into the environment. Larvae of T. molitor can eat inorganic materials like styrofoam and organic ones like bran. The ability to do this is demonstrated by the growth of the larvae's weight and length, with the rise in larval length in each treatment having the most beneficial result.